International evaluation of current practices in cognitive assessment for motor neurone disease. (2nd February 2022) - Gray, Debbie; Abrahams, Sharon
Abstract : Background: Motor Neurone Disease (MND) is a rapidly progressive neurodegenerative disease, with up to 50% suffering from cognitive and/or behaviour changes. Aims: Evaluate current practices in the cognitive assessment of MND patients internationally. Methods: An online survey explored the use of cognitive assessments in MND clinics. Findings: 80/195 clinicians responded. The Edinburgh Cognitive and Behavioural ALS Screen (ECAS) was the most popular method for evaluating cognition and 72% agreed that patients screened for cognitive change have better clinical care. Thematic analysis of open-ended responses indicated that cognitive assessments help to: identify and validate changes in cognition and behaviour, aid understanding of the clinical impact of the disease, inform and direct clinical care, and infer patients' decision-making abilities. However, a number of factors affected the implementation and administration of cognitive assessments in clinics. Conclusions: Cognitive assessments have been implemented in MND clinics internationally and have a positive impact on clinical practice.